2017
DOI: 10.1590/1678-992x-2016-0290
|View full text |Cite
|
Sign up to set email alerts
|

Dry matter intake, performance and carcass characteristics of hair sheep reared under different grazing systems

Abstract: The aim of this study was to evaluate the effect of three different grazing systems: isolated, alternate and simultaneous, on feed intake, performance and carcass characteristics of sheep. About 5.2 ha area of Tanzania grass (Panicum maximun Jacq cultivate Tanzania) was divided into 13 paddocks. This area was used as a stocking rate of two animal units (AU) per ha for 7 days' occupation and 21 days rest. A total number of 58 animals were used consisting of 12 heifers and 30 Santa Ines lambs with the addition o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 28 publications
2
9
0
1
Order By: Relevance
“…The BWG of the lambs fed the NG diet was similar to those fed the CCs and PSs diets. These results agree with Santos et al [21] who found that BWG was affected by DMI. The high NDF and ADF contents (Table-1) in the agricultural by-product diets did not significantly decrease lamb productivity.…”
Section: Feed Intake Digestibility Bwg Fcr and Economic Implicationssupporting
confidence: 93%
See 1 more Smart Citation
“…The BWG of the lambs fed the NG diet was similar to those fed the CCs and PSs diets. These results agree with Santos et al [21] who found that BWG was affected by DMI. The high NDF and ADF contents (Table-1) in the agricultural by-product diets did not significantly decrease lamb productivity.…”
Section: Feed Intake Digestibility Bwg Fcr and Economic Implicationssupporting
confidence: 93%
“…The carcass weights obtained in this study were similar to those reported by Setyaningrum et al [26], where Indonesian thin-tailed sheep weighing 17.5-18.8 kg produced 7.7-8.5 kg carcasses. Other studies reported that lamb carcass weights varied from 15.3 kg to 26.1 kg when originating from a slaughter weight of 34.3 kg-54.1 kg [21,[27][28][29][30]. Forwood et al [30] reported that heavier live weights produced higher carcass weights and dressing percentages.…”
Section: Carcass Characteristicsmentioning
confidence: 99%
“…The influence of better nutrient density and quality of nutrient available for feed utilization and physiological state of animals on test diets might explain why animals on GK B , GK C and GK D were higher in total and daily weight gains than those on GK A . It has been evident that better feed quality diets with a possible increase in the digestibility provide better weight gain for animals (Santos et al, 2017). The observed trend in feed intake (Table 5) that decreased gradually with increased in Garcinia kola could be attributed to the palatability, physical and chemical forms of the diets.…”
Section: Discussionmentioning
confidence: 96%
“…Pertambahan bobot badan dan bobot badan saat sapih anak domba yang mendapatkan asupan susu yang berasal dari induknya (PSI) lebih tinggi (P<0,05) berturut-turut yaitu 115,7 g/ekor/hari dan 8,3 kg/ekor dibandingkan dengan anak domba yang diberikan milk replacer (PMR) yaitu 61,5 g/ekor/hari dan 6,8 kg/ekor. Pertumbuhan berkorelasi positif dengan jumlah konsumsi dan kualitas pakan (dos Santos, 2017).…”
Section: Pertambahan Bobot Badan Pra Sapih Dan Bobot Badan Saat Sapihunclassified